Steel and carburized steel parts

A steel material with optimized chemical composition and microstructure addresses the challenge of achieving high bending and surface fatigue strength in carburized parts through controlled cementite formation during vacuum carburizing, enhancing performance in power units and mechanical parts.

JP7606077B2Active Publication Date: 2024-12-25NIPPON STEEL CORPORATION
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020191379
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-18
Publication Date
2024-12-25
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

Existing steel materials used for carburized steel parts do not adequately address the need for high bending fatigue strength and surface fatigue strength, particularly in vacuum carburizing processes, where grain boundary oxidation layers are suppressed, and the formation of cementite is critical for hardness and strength.

Method used

A steel material with specific chemical compositions and microstructural requirements, including ranges for elements like C, Si, Mn, Cr, Mo, and Al, optimized to form an appropriate hardened layer with controlled cementite formation during vacuum carburizing, ensuring adequate carbon diffusion and hardness.

Benefits of technology

The steel material achieves enhanced bending fatigue strength and surface fatigue strength in carburized parts, with a hardened layer that maintains hardness and resistance to cracking, suitable for applications in power units and mechanical parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606077000003
    Figure 0007606077000003
  • Figure 0007606077000004
    Figure 0007606077000004
  • Figure 0007606077000005
    Figure 0007606077000005
Patent Text Reader

Abstract

To provide a steel that undergoes vacuum carburization into a carburized steel component, which exhibits excellent bending fatigue strength and surface fatigue strength (pitching properties).SOLUTION: A steel consists of, in mass%, C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P: 0.030% or less, S: 0.050% or less, Ni: 0.01-0.20%, Cr: 0.65-1.50%, Mo: 0.01-0.60%, Al: 0.045% or less, and N: 0.0250% or less, with the balance being Fe and impurities, satisfying formula (1)-formula (4): 2.5≤(2Mn+5Cr+Mo) / Si≤7.5 (1), Mn×Ni≤0.05 (2), 1.7≤Al / N≤2.4 (3), 22≤Mn / S≤65 (4), where, each element symbol in the formula (1)-formula (4) is substituted for by the content of a corresponding element in mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a steel material suitable for use as a material for carburized steel parts, and to carburized steel parts. [Background technology]

[0002] In recent years, with the increase in output and miniaturization of power units such as engines and motors, excellent bending fatigue strength is required for power units and mechanical parts used around the power units. Among these mechanical parts, gears used in automobiles, construction vehicles, etc. have tooth surfaces that slide against each other at short intervals. Therefore, pitting must be suppressed on the tooth surfaces. In other words, mechanical parts such as gears used in automobiles, construction vehicles, etc. are required to have not only bending fatigue strength but also surface fatigue strength (pitting characteristics).

[0003] Carburizing is known as a method for increasing the bending fatigue strength and surface fatigue strength of mechanical parts. In this specification, carburizing includes not only carburizing but also carbonitriding. In carburizing, a hardened layer (carburized layer or carbonitriding layer) is formed on the surface of the mechanical part. It is known that this hardened layer increases the bending fatigue strength and surface fatigue strength of the mechanical part. Therefore, it is required that the steel material used for carburized steel parts can have higher bending fatigue strength and surface fatigue strength when the mechanical part (carburized steel part) is made by carburizing.

[0004] Steel materials that can increase bending fatigue strength and surface fatigue strength when carburized to form carburized steel parts are proposed in JP 2010-185123 A (Patent Document 1) and JP 2017-214642 A (Patent Document 2).

[0005] The steel material disclosed in Patent Document 1 contains, by mass%, C: 0.15 to 0.25%, Si: 0.40 to 0.80%, Mn: 0.20 to 1.0%, P: 0.030% or less, S: 0.10% or less, Cu: 0.30% or less, Ni: 0.30% or less, Cr: 0.8 to 1.8%, Mo: 0.60% or less, Al: 0.02 to 0.10%, N: 0.005 to 0.03%, O: 0.003% or less, with the balance being Fe and unavoidable impurities, and satisfies the following formulas (1) and (2). 1.8≦2×[Si]+[Cr]≦3.5 (1) 114×[Si]+2×[Cr]+68×[Mo]≧50 (2)

[0006] The steel material disclosed in Patent Document 2 contains, by mass%, C: 0.15 to 0.30%, Si: 0.80% to 2.00%, Mn: 0.20 to 0.80%, P: 0.003 to 0.030%, S: 0.005 to 0.050%, Cr: 1.00 to less than 1.80%, Mo: 0.03 to 0.30%, Al: 0.020 to 0.060%, N: 0.0060 to 0.0300%, and O: 0.0003 to 0.0025%, with the balance being Fe and unavoidable impurities, and satisfies the following formulas (1) to (3). [%Si]+([%Mn]+[%Cr]+[%Mo]) / 3≧1.5 (1) 180-45[%Mn]-14[%Cr]-51[%Mo]+5[%Si]≧125 (2) √I≦80 (3) Here, I is the area (μm2) of oxide inclusions located at the center of fisheyes on the fracture surface after the steel material is carburized, quenched, and tempered, and then subjected to a rotating bending fatigue test. 2 ) is shown. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2010-185123 A [Patent Document 2] JP 2017-214642 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, there may be a steel material that can obtain excellent bending fatigue strength and excellent surface fatigue strength when carburized to form a carburized steel part by a means different from that proposed in Patent Documents 1 and 2. In addition, carburizing treatment includes gas carburizing treatment and vacuum carburizing treatment. In vacuum carburizing treatment, carburizing is performed in a vacuum or under reduced pressure. Therefore, in vacuum carburizing treatment, the formation of a grain boundary oxide layer on the surface layer, which is a problem in gas carburizing treatment, can be suppressed. Therefore, in steel materials used in vacuum carburizing treatment, the content of elements that easily form oxides, such as Si, Cr, and Mn, which promote the formation of a grain boundary oxide layer, can be increased in gas carburizing treatment. Therefore, there is a demand for a steel material suitable for vacuum carburizing treatment and which can be used as a material for carburized steel parts.

[0009] An object of the present disclosure is to provide a steel material and a carburized steel part that, when subjected to vacuum carburization treatment to form a carburized steel part, exhibit excellent bending fatigue strength and excellent surface fatigue strength (pitting characteristics). [Means for solving the problem]

[0010] The steel material according to the present disclosure is Chemical composition in mass percent: C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P:0.030% or less, S: 0.050% or less, Ni: 0.01 to 0.20%, Cr: 0.65-1.50%, Mo: 0.01 to 0.60%, Al: 0.045% or less, and N: 0.0250% or less, and the balance being Fe and impurities, and satisfying formulas (1) to (4). 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn×Ni≦0.05 (2) 1.7≦Al / N≦2.4 (3) 22≦Mn / S≦65 (4) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (4).

[0011] The carburized steel component according to the present disclosure comprises: A hardened layer; A core portion is provided inside the hardened layer, The chemical composition of the core is, in mass%, C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P:0.030% or less, S: 0.050% or less, Ni: 0.01 to 0.20%, Cr: 0.65-1.50%, Mo: 0.01 to 0.60%, Al: 0.045% or less, and N: 0.0250% or less, and the balance being Fe and impurities, and satisfying formulas (1) to (4), The carbon concentration in a region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more by mass%, The microstructure of the carburized steel part at a depth of 20 μm from the surface is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn×Ni≦0.05 (2) 1.7≦Al / N≦2.4 (3) 22≦Mn / S≦65 (4) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (4). Effect of the Invention

[0012] When the steel material according to the present disclosure is subjected to a vacuum carburizing process to form a carburized steel part, excellent bending fatigue strength and excellent surface fatigue strength (pitting properties) can be obtained. The carburized steel part according to the present disclosure has excellent bending fatigue strength and excellent surface fatigue strength. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a diagram showing an example of a heat pattern in the vacuum carburizing process and the quenching process. [Diagram 2] FIG. 2 is a side view of a small roller test piece prepared in the example. [Diagram 3] FIG. 3 is a side view of a rotating bending fatigue test piece prepared in the example. [Figure 4] FIG. 4 is a front view of a large roller test piece prepared in the example. [Diagram 5] FIG. 5 is a schematic diagram of a twin roller rolling fatigue test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present inventors have conducted research into steel materials that can provide excellent bending fatigue strength and excellent surface fatigue strength (pitting properties) when they are made into carburized steel parts by vacuum carburizing (vacuum carburizing or vacuum carbonitriding). Such steel materials are subjected to the vacuum carburizing process, for example, as described above, in the manufacturing process of the carburized steel parts. In the vacuum carburizing process, the steel material is subjected to A c3Since the steel is heated to above its transformation temperature, the microstructure of the steel is transformed into austenite, and the influence of the previous structure is eliminated. Therefore, the inventors of the present invention have investigated ways to increase the bending fatigue strength and surface fatigue strength of carburized steel parts not from the viewpoint of the microstructure of the steel, but from the viewpoint of the chemical composition that remains unchanged even when vacuum carburization is performed. As a result, the inventors of the present invention have concluded that it is effective to increase the contents of Si, Cr, Mn, and Mo, which increase temper softening resistance, in order to increase the surface fatigue strength (pitting characteristics). Then, the compatibility of bending fatigue strength and surface fatigue strength was examined from the viewpoint of chemical composition, and the results were as follows: C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P: 0.030% or less, S: 0.050% or less, Ni: 0.01-0.20%, Cr: 0.65-1.50%, Mo: 0.01-0.60%, Al: 0.045% or less, N: 0.0250% or less, V: 0-0.50%, Nb: 0-0.030%, Ti: 0-0.200%, Cu: 0-0.50%, W: 0-0.50%, ... It was believed that if a steel material had a chemical composition consisting of O: 0-0.50%, B: 0-0.0010%, Ca: 0-0.0015%, Mg: 0-0.010%, rare earth elements (REM): 0-0.0100%, Te: 0-0.100%, Bi: 0-0.500%, Pb: 0-0.09%, Sn: 0-0.015%, and Sb: 0-0.006%, with the balance being Fe and impurities, then when a carburized steel part is manufactured by performing a vacuum carburizing process, the carburized steel part will have excellent bending fatigue strength and excellent surface fatigue strength.

[0015] However, even when the contents of the elements in the chemical composition of steel are within the above-mentioned ranges, there are cases where sufficient bending fatigue strength and surface fatigue strength cannot be obtained when the steel is subjected to vacuum carburization to produce a carburized steel part. Therefore, the present inventors have further investigated and studied the matter. As a result, the present inventors have come to the following findings.

[0016] (A) In the vacuum carburizing process, a carburizing step and a diffusion step are performed once each in a vacuum or under reduced pressure, or the carburizing step and the diffusion step are alternately repeated multiple times. In the carburizing step, a hydrocarbon-based gas is introduced at low pressure to form an appropriate amount of cementite on the surface layer of the steel material. Then, in the diffusion step, the introduction of the hydrocarbon-based gas is stopped. In this case, the cementite decomposes in the diffusion step, and the carbon concentration in the surface layer of the steel material increases due to the decomposition of the cementite. As a result, in the diffusion step of the vacuum carburizing process, the gradient of the carbon concentration in the austenite in the surface layer becomes larger compared to the diffusion step of the gas carburizing process, and the amount of C penetrating into the inside of the steel material can be increased. In this way, in the diffusion step of the vacuum carburizing process, no hydrocarbon-based gas is introduced, and the cementite formed on the surface layer of the steel material in the previous carburizing process is used as a carbon (C) supply source to diffuse and penetrate C into the inside of the steel material. As a result, the vacuum carburizing process can form a hardened layer in a short time compared to the gas carburizing process.

[0017] As described above, Si, Cr, Mn, and Mo are all elements that increase the temper softening resistance of steel and increase the surface fatigue strength (pitting characteristics). Here, Mn, Cr, and Mo all have high affinity with C, and tend to form cementite and alloy carbides (hereinafter referred to as cementite, etc.) on the surface layer of the steel during the carburizing process of the vacuum carburizing treatment. On the other hand, Si has low affinity with C, and tends to form cementite, etc. on the surface layer of the steel during the carburizing process of the vacuum carburizing treatment.

[0018] If the Si content is too high relative to the Mn, Cr, and Mo contents in the temperature range in which the vacuum carburizing process is performed, cementite and the like are difficult to form on the surface layer of the steel during the carburizing process of the vacuum carburizing process. In this case, there is a shortage of cementite and the like that serves as a C supply source during the diffusion process. As a result, the gradient of C concentration between the surface and the interior of the steel is small. As a result, the penetration and diffusion of C into the interior of the steel is insufficient. As a result, it becomes difficult to form a hardened layer, and the surface fatigue strength of the carburized steel part decreases.

[0019] On the other hand, if the contents of Cr, Mn, and Mo are too high relative to the Si content, cementite and the like are formed excessively in the carburizing process of the vacuum carburizing treatment. In this case, although a certain amount of cementite and the like is decomposed in the diffusion process, some of the cementite and the like remains in the surface layer without being decomposed. Cementite and the like become the starting point of cracks in bending fatigue. Therefore, if an excessive amount of cementite and the like remains in the surface layer, the bending fatigue strength of the carburized steel part is reduced.

[0020] By setting the ratio of the Cr, Mn and Mo contents to the Si content within an appropriate range, the C concentration penetrating into the steel material during the carburizing process of the vacuum carburizing treatment is within an appropriate range. As a result, a hardened layer with a sufficient C concentration can be stably formed on the surface of the carburized steel part. As a result, the bending fatigue strength and surface fatigue strength of the carburized steel part can be improved.

[0021] It is defined as F1 = (2Mn + 5Cr + Mo) / Si. If the content of each element in the chemical composition is within the above-mentioned range and F1 is 2.5 to 7.5, that is, if the following formula (1) is satisfied, the Si content relative to the contents of Mn, Cr, and Mo is in an appropriate range. Therefore, an appropriate amount of C penetrates and diffuses into the steel material during vacuum carburization. As a result, carburized steel parts manufactured using the steel material as a material can obtain excellent bending fatigue strength and excellent surface fatigue strength, provided that the content of each element in the chemical composition is within the above-mentioned range and satisfies the below-mentioned formulas (2) to (4). 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1)

[0022] (B) Even if an appropriate amount of C penetrates and diffuses into a steel material satisfying formula (1) in the temperature range in which the vacuum carburizing process is carried out, if the amount of retained austenite in the surface layer of the steel material after the vacuum carburizing process is excessively high, sufficient hardness cannot be obtained and bending fatigue strength may decrease. Therefore, the present inventors conducted further studies and obtained the following findings.

[0023] Mn and Ni are austenite stabilizing elements, and both increase the amount of retained austenite in the surface layer of the steel after vacuum carburization. Therefore, even if the content of each element in the chemical composition is within the above-mentioned range and formula (1) is satisfied, if the Mn content and Ni content are not appropriately adjusted, excessive retained austenite will exist in the surface layer of the steel after vacuum carburization. In this case, the carburized steel part will not have sufficient hardness and will not have sufficient bending fatigue strength.

[0024] F2 is defined as Mn x Ni. If F2 is 0.05 or less, that is, if the following formula (2) is satisfied, the amount of retained austenite in the surface layer of the carburized steel part can be set to an appropriate range, provided that the content of each element in the chemical composition is within the above-mentioned range and formulas (1), (3) and (4) are satisfied. Therefore, a hardened layer with sufficient surface hardness is formed. As a result, the carburized steel part can obtain sufficient bending fatigue strength. Mn×Ni≦0.05 (2)

[0025] (C) Even if the content of each element in the chemical composition is within the above-mentioned range, if there are excessive Al inclusions in the steel, the Al inclusions can become the starting point of cracks. Therefore, if there are excessive Al inclusions remaining in the steel, the bending fatigue strength of the carburized steel part may decrease. Furthermore, Al in the steel may precipitate as precipitates (AlN). Coarse AlN (precipitates) can become the starting point of cracks, just like Al inclusions. Therefore, if there are excessively large amounts of coarse AlN (precipitates) remaining in the steel, the bending fatigue strength of the carburized steel part may decrease.

[0026] F3 is defined as Al / N. In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F3 is less than 1.7, the Al content is excessively high compared to the N content. In this case, an excessive amount of Al inclusions (oxidation-based inclusions) that are not bonded with N are formed. As a result, the bending fatigue strength of the carburized steel part is reduced.

[0027] On the other hand, in the chemical composition of the steel material of this embodiment, if F3 exceeds 2.4, assuming that the content of each element is within the range of this embodiment, the N content is excessively higher than the Al content. In this case, excessively large coarse AlN (precipitates) are formed in the steel material. Therefore, in this case as well, the bending fatigue strength of the carburized steel part is reduced.

[0028] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F3 is 1.7 to 2.4, that is, if the following formula (3) is satisfied, the formation of Al inclusions in the steel material can be sufficiently suppressed, and the formation of coarse AlN (precipitates) can be sufficiently suppressed. Therefore, assuming that formulas (1), (2), and (4) are satisfied, sufficient bending fatigue strength can be obtained in the carburized steel part. 1.7≦Al / N≦2.4 (3)

[0029] (D) When the content of each element in the chemical composition is within the above-mentioned range, Mn combines with S to form MnS. MnS improves the machinability of steel. However, coarse MnS becomes the starting point of cracks during bending fatigue of carburized steel parts. Therefore, if an excessive amount of coarse MnS is formed, the bending fatigue strength of the carburized steel parts decreases. Therefore, if the ratio of Mn content to S content can be appropriately adjusted to suppress the formation of coarse MnS, the bending fatigue strength of the carburized steel parts can be increased.

[0030] F4 is defined as F4=Mn / S. If F4 is 22-65, that is, if the following formula (4) is satisfied, the formation of coarse MnS can be effectively suppressed. As a result, on the premise that the content of each element in the chemical composition is within the above-mentioned range and formulas (1) to (3) are satisfied, sufficient surface fatigue strength and sufficient bending fatigue strength can be obtained in the carburized steel part. 22≦Mn / S≦65 (4)

[0031] The steel material and carburized steel part of this embodiment have been completed based on the above technical concept, and have the following configuration.

[0032] [1] Chemical composition in mass percent: C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P:0.030% or less, S: 0.050% or less, Ni: 0.01 to 0.20%, Cr: 0.65-1.50%, Mo: 0.01 to 0.60%, Al: 0.045% or less, and N: 0.0250% or less, and the balance being Fe and impurities, and satisfying formulas (1) to (4). Steel material. 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn×Ni≦0.05 (2) 1.7≦Al / N≦2.4 (3) 22≦Mn / S≦65 (4) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (4).

[0033] [2] [1] The steel material according to the present invention The chemical composition is such that, in place of a portion of Fe, V: 0.50% or less, Nb: 0.030% or less, Ti: 0.200% or less, Cu: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, and B: 0.0010% or less, Contains one or more selected from the group consisting of Steel material.

[0034] [3] The steel material according to [1] or [2], The chemical composition is such that, in place of a portion of Fe, Ca: 0.0015% or less, Mg: 0.010% or less, and Rare earth elements: 0.0100% or less, Contains one or more selected from the group consisting of Steel material.

[0035] [4] The steel material according to any one of [1] to [3], The chemical composition is such that, in place of a portion of Fe, Te: 0.100% or less, Bi: 0.500% or less, Pb: 0.09% or less, Sn: 0.015% or less, and Sb: 0.006% or less, Contains one or more selected from the group consisting of Steel material.

[0036] [5] A carburized steel part, A hardened layer; A core portion is provided inside the hardened layer, The chemical composition of the core is, in mass%, C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P:0.030% or less, S: 0.050% or less, Ni: 0.01 to 0.20%, Cr: 0.65-1.50%, Mo: 0.01 to 0.60%, Al: 0.045% or less, and N: 0.0250% or less, and the balance being Fe and impurities, and satisfying formulas (1) to (4), The carbon concentration in a region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more by mass%, The microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. Carburized steel parts. 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn×Ni≦0.05 (2) 1.7≦Al / N≦2.4 (3) 22≦Mn / S≦65 (4) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (4).

[0037] [6] A carburized steel part according to [5], The chemical composition of the core portion is, in place of a part of Fe, V: 0.50% or less, Nb: 0.030% or less, Ti: 0.200% or less, Cu: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, and B: 0.0010% or less, Contains one or more selected from the group consisting of Carburized steel parts.

[0038] [7] A carburized steel part according to [5] or [6], The chemical composition of the core portion is, in place of a part of Fe, Ca: 0.0015% or less, Mg: 0.0100% or less, and Rare earth elements: 0.0100% or less, Contains one or more selected from the group consisting of Carburized steel parts.

[0039] [8] A carburized steel part according to any one of [5] to [7], The chemical composition of the core portion is, in place of a part of Fe, Te: 0.100% or less, Bi: 0.500% or less, Pb: 0.09% or less, Sn: 0.015% or less, and Sb: 0.006% or less, Contains one or more selected from the group consisting of Carburized steel parts.

[0040] The steel material according to this embodiment and the carburized steel part manufactured using this steel material as a raw material will be described in detail below. The "%" for the content of each element means "mass %" unless otherwise specified.

[0041] [Steel use] The steel material of this embodiment is suitable as a material for carburized steel parts. Specifically, the steel material of this embodiment is suitable as a material for carburized steel parts manufactured by carrying out a vacuum carburizing process. In this specification, the vacuum carburizing process also includes a vacuum carbonitriding process.

[0042] [Chemical composition of steel] The chemical composition of the steel material of this embodiment contains the following elements.

[0043] C: 0.10-0.35% Carbon (C) improves the hardenability of steel and increases the hardness of the core of carburized steel parts manufactured using the steel material. Therefore, C increases the bending fatigue strength of the carburized steel parts. If the C content is less than 0.10%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content exceeds 0.35%, the machinability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the C content is 0.10 to 0.35%. The preferred lower limit of the C content is 0.11%, more preferably 0.12%, and even more preferably 0.13%. The preferred upper limit of the C content is 0.32%, more preferably 0.30%, and even more preferably 0.28%.

[0044] Silicon: 0.60 to 1.50% Silicon (Si) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting properties) of carburized steel parts manufactured using the steel as a raw material. If the Si content is less than 0.60%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content exceeds 1.50%, even if the contents of other elements are within the range of this embodiment, the formation of cementite and the like (cementite and alloy carbides) is inhibited in the temperature range of the vacuum carburization treatment. In this case, the penetration of C into the steel material is suppressed during the vacuum carburization treatment. Therefore, the depth of the surface layer (hardened layer) of the carburized steel part decreases, and the surface fatigue strength decreases. Therefore, the Si content is 0.60 to 1.50%. The preferable lower limit of the Si content is 0.65%, more preferably 0.70%, more preferably 0.75%, more preferably 0.80%, more preferably 0.85%, and more preferably 0.90%. The upper limit of the Si content is preferably 1.45%, more preferably 1.40%, further preferably 1.35%, and further preferably 1.30%.

[0045] Mn: 0.20 to 1.30% Manganese (Mn) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting properties) of carburized steel parts manufactured using the steel material as a raw material. If the Mn content is less than 0.20%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content exceeds 1.30%, the amount of retained austenite in the surface layer of the carburized steel part after the vacuum carburization treatment becomes too high even if the contents of other elements are within the range of this embodiment. In this case, the hardness of the carburized steel part is not sufficient, and the bending fatigue strength of the carburized steel part decreases. Therefore, the Mn content is 0.20 to 1.30%. The preferable lower limit of the Mn content is 0.25%, more preferably 0.30%, more preferably 0.35%, more preferably 0.40%, and even more preferably 0.45%. The upper limit of the Mn content is preferably 1.25%, more preferably 1.20%, more preferably 1.15%, more preferably 1.10%, more preferably 1.05%, and more preferably 1.00%.

[0046] P:0.030% or less Phosphorus (P) is an impurity. In a vacuum carburizing process when a carburized steel part is manufactured using a steel material as a base material, P segregates at the austenite grain boundaries, reducing the bending fatigue strength of the carburized steel part. If the P content exceeds 0.030%, the bending fatigue strength of the carburized steel part is significantly reduced even if the contents of other elements are within the range of this embodiment. Therefore, the P content is 0.030% or less. The preferred upper limit of the P content is 0.029%, more preferably 0.028%, and even more preferably 0.025%. The P content is preferably as low as possible. However, excessive reduction of the P content increases the manufacturing cost. Therefore, in consideration of normal industrial production, the preferred lower limit of the P content is more than 0%, more preferably 0.001%, and even more preferably 0.002%.

[0047] S: 0.050% or less Sulfur (S) is an impurity. S combines with Mn to form MnS, which improves the machinability of steel. However, if the S content exceeds 0.050%, the sulfides become coarse even if the contents of other elements are within the range of this embodiment. In this case, the bending fatigue strength of the carburized steel part decreases. Therefore, the S content is 0.050% or less. The preferred lower limit of the S content is more than 0%, more preferably 0.001%, more preferably 0.002%, more preferably 0.005%, and more preferably 0.007%. The preferred upper limit of the S content is 0.045%, more preferably 0.040%, more preferably 0.035%, and more preferably 0.030%.

[0048] Ni: 0.01 to 0.20% Nickel (Ni) improves the hardenability of steel and increases the hardness of the core of the carburized steel part manufactured from the steel material. As a result, the bending fatigue strength of the carburized steel part is increased. If the Ni content is less than 0.01%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ni content exceeds 0.20%, the volume fraction of the retained austenite in the surface layer of the carburized steel part becomes excessively large even if the contents of other elements are within the range of this embodiment. As a result, the bending fatigue strength of the carburized steel part decreases. Therefore, the Ni content is 0.01 to 0.20%. The preferred lower limit of the Ni content is 0.02%, more preferably 0.03%, and more preferably 0.04%. The preferred upper limit of the Ni content is 0.17%, more preferably 0.14%, and more preferably 0.11%.

[0049] Cr: 0.65~1.50% Chromium (Cr) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting characteristics) of carburized steel parts manufactured using the steel as a raw material. If the Cr content is less than 0.65%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content exceeds 1.50%, C penetrates and diffuses excessively into the steel in the vacuum carburizing treatment even if the contents of other elements are within the range of this embodiment. As a result, coarse cementite is excessively generated in the surface layer of the steel. In this case, even in the diffusion process of the vacuum carburizing treatment, some of the coarse cementite remains without being decomposed. As a result, cracks are likely to occur starting from the coarse cementite in the carburized steel part, and the bending fatigue strength of the carburized steel part is reduced. Therefore, the Cr content is 0.65 to 1.50%. The preferable lower limit of the Cr content is 0.70%, more preferably 0.75%, more preferably 0.80%, and even more preferably 0.85%. The upper limit of the Cr content is preferably 1.45%, more preferably 1.40%, further preferably 1.35%, and further preferably 1.30%.

[0050] Mo: 0.01 to 0.60% Molybdenum (Mo) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting properties) of carburized steel parts manufactured using the steel as a raw material. If the Mo content is less than 0.01%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mo content exceeds 0.60%, C penetrates and diffuses excessively into the steel in the vacuum carburizing treatment even if the contents of other elements are within the range of this embodiment. As a result, coarse cementite is excessively generated in the surface layer of the steel. In this case, even in the diffusion process of the vacuum carburizing treatment, some of the coarse cementite remains without being decomposed. As a result, cracks are likely to occur starting from the coarse cementite in the carburized steel part, and the bending fatigue strength of the carburized steel part is reduced. Therefore, the Mo content is 0.01 to 0.60%. The preferable lower limit of the Mo content is 0.02%, more preferably 0.03%, more preferably 0.04%, and even more preferably 0.05%. The upper limit of the Mo content is preferably 0.55%, more preferably 0.50%, and further preferably 0.45%.

[0051] Al: 0.045% or less Aluminum (Al) deoxidizes steel. However, if the Al content exceeds 0.045%, coarse Al inclusions (oxide-based inclusions) are generated even if the contents of other elements are within the range of this embodiment. The coarse Al inclusions reduce the bending fatigue strength of the carburized steel parts. Therefore, the Al content is 0.045% or less. The preferred lower limit of the Al content is more than 0%, more preferably 0.001%, more preferably 0.005%, and even more preferably 0.010%. The preferred upper limit of the Al content is 0.042%, more preferably 0.039%, more preferably 0.036%, and even more preferably 0.033%.

[0052] N: 0.0250% or less Nitrogen (N) is an impurity. If the N content exceeds 0.0250%, coarse nitrides, such as AlN, will be generated even if the contents of other elements are within the range of this embodiment. The coarse nitrides reduce the bending fatigue strength of the carburized steel parts. Therefore, the N content is 0.0250% or less. The preferred upper limit of the N content is 0.0230%, more preferably 0.0210%, more preferably 0.0200%, more preferably 0.0190%, and more preferably 0.0180%. The N content is preferably as low as possible. However, if the N content is reduced excessively, the manufacturing cost will increase. Therefore, in consideration of normal industrial production, the preferred lower limit of the N content is more than 0%, more preferably 0.0001%, and more preferably 0.0005%.

[0053] The balance of the chemical composition of the steel material according to the present embodiment is composed of Fe and impurities. Here, the term "impurities" refers to substances that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of the steel material, and are permissible within a range that does not adversely affect the steel material according to the present embodiment.

[0054] [Optional elements] The steel material of this embodiment may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of V, Nb, Ti, Cu, W, Co, and B. All of these elements are optional elements, and they increase the bending fatigue strength of a carburized steel part manufactured using the steel material as a material.

[0055] V: 0.50% or less Vanadium (V) is an optional element and may not be contained. In other words, the V content may be 0%. When vanadium (V) is contained, that is, when the V content is more than 0%, V forms precipitates (carbides, nitrides, carbonitrides, etc.) and suppresses the coarsening of crystal grains of steel during vacuum carburization treatment due to the pinning effect. As a result, the bending fatigue strength of carburized steel parts manufactured using the steel as a material is increased. If even a small amount of V is contained, the above effect can be obtained to a certain extent. However, if the V content exceeds 0.50%, the hardness of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel decreases. Therefore, the V content is 0 to 0.50%, and when contained, it is 0.50% or less. The preferable lower limit of the V content is 0.01%, more preferably 0.05%, and more preferably 0.10%. The preferable upper limit of the V content is 0.40%, and more preferably 0.30%.

[0056] Nb: 0.030% or less Niobium (Nb) is an optional element and may not be contained. That is, the Nb content may be 0%. When it is contained, that is, when the Nb content is more than 0%, Nb forms precipitates (carbides, carbonitrides, etc.) and suppresses the coarsening of crystal grains of steel during vacuum carburization treatment due to the pinning effect. As a result, the bending fatigue strength of carburized steel parts manufactured using the steel as a raw material is increased. If even a small amount of Nb is contained, the above effect can be obtained to a certain extent. However, if the Nb content exceeds 0.030%, even if the contents of other elements are within the range of this embodiment, the Nb precipitates become coarse and the pinning effect cannot be obtained. Therefore, the Nb content is 0 to 0.030%, and when it is contained, it is 0.030% or less. The preferable lower limit of the Nb content is 0.001%, and more preferably 0.005%. The preferable upper limit of the Nb content is 0.027%, more preferably 0.025%, and more preferably 0.020%.

[0057] Ti: 0.200% or less Titanium (Ti) is an optional element and may not be contained. In other words, the Ti content may be 0%. When titanium is contained, that is, when the Ti content is more than 0%, Ti forms precipitates (carbides, nitrides, carbonitrides, etc.) and suppresses the coarsening of crystal grains of steel during vacuum carburization treatment due to the pinning effect. As a result, the bending fatigue strength of carburized steel parts manufactured using steel as a raw material is increased. If even a small amount of Ti is contained, the above effect can be obtained to a certain extent. However, if the Ti content exceeds 0.200%, even if the contents of other elements are within the range of this embodiment, the Ti precipitates become coarse and the pinning effect cannot be obtained. Therefore, the Ti content is 0 to 0.200%, and when contained, it is 0.200% or less. The preferable lower limit of the Ti content is 0.001%, more preferably 0.005%, and even more preferably 0.010%. The upper limit of the Ti content is preferably 0.180%, more preferably 0.160%, more preferably 0.140%, more preferably 0.120%, and even more preferably 0.100%.

[0058] Cu: 0.50% or less Copper (Cu) is an optional element and may not be contained. In other words, the Cu content may be 0%. When copper is contained, that is, when the Cu content is more than 0%, Cu enhances the hardenability of the steel and enhances the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Cu is contained, the above effect can be obtained to some extent. However, if the Cu content exceeds 0.50%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cu content is 0 to 0.50%, and if contained, it is 0.50% or less. The preferred lower limit of the Cu content is 0.01%, more preferably 0.05%, more preferably 0.08%, and more preferably 0.10%. The preferred upper limit of the Cu content is 0.48%, and more preferably 0.46%.

[0059] W: 0.50% or less Tungsten (W) is an optional element and may not be contained. That is, the W content may be 0%. When it is contained, that is, when the W content is more than 0%, W increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of W is contained, the above effect can be obtained to a certain extent. However, if the W content exceeds 0.50%, the strength of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel decreases. Therefore, the W content is 0 to 0.50%, and when it is contained, it is 0.50% or less. The preferable lower limit of the W content is 0.01%, more preferably 0.05%, and more preferably 0.08%. The preferable upper limit of the W content is 0.40%, and more preferably 0.30%.

[0060] Co:0.50% or less Cobalt (Co) is an optional element and may not be contained. That is, the Co content may be 0%. When it is contained, that is, when the Co content is more than 0%, Co increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Co is contained, the above effect can be obtained to a certain extent. However, if the Co content exceeds 0.50%, the strength of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel decreases. Therefore, the Co content is 0 to 0.50%, and if it is contained, it is 0.50% or less. The preferred lower limit of the Co content is 0.01%, more preferably 0.05%, and more preferably 0.08%. The preferred upper limit of the Co content is 0.40%, and more preferably 0.30%.

[0061] B: 0.0010% or less Boron (B) is an optional element and may not be contained. In other words, the B content may be 0%. When it is contained, that is, when the B content is more than 0%, B increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel material as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of B is contained, the above effect can be obtained to a certain extent. However, if the B content exceeds 0.0010%, the effect is saturated. Therefore, the B content is 0 to 0.0010%, and if contained, it is 0.0010% or less. The preferable lower limit of the B content is 0.0001%, more preferably 0.0002%, and more preferably 0.0003%. The preferable upper limit of the B content is 0.0009%, and more preferably 0.0008%.

[0062] The steel material of this embodiment may further contain one or more elements selected from the group consisting of Ca, Mg, and rare earth elements (REM) in place of a portion of Fe. All of these elements are optional elements, and increase the bending fatigue strength of a carburized steel part manufactured using the steel material as a material.

[0063] Ca: 0.0015% or less Calcium (Ca) is an optional element and may not be contained. In other words, the Ca content may be 0%. When it is contained, that is, when the Ca content is more than 0%, Ca modifies the sulfides in the steel material and inhibits the sulfides from elongating during hot working. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Ca is contained, the above effect can be obtained to a certain extent. However, if the Ca content exceeds 0.0015%, the above effect is saturated. Therefore, the Ca content is 0 to 0.0015%, and if contained, it is 0.0015% or less. The preferable lower limit of the Ca content is 0.0001%, and more preferably 0.0002%. The preferable upper limit of the Ca content is 0.0012%, and more preferably 0.0010%.

[0064] Mg: 0.010% or less Magnesium (Mg) is an optional element and may not be contained. That is, the Mg content may be 0%. When magnesium is contained, that is, when the Mg content is more than 0%, Mg modifies sulfides in the steel material and inhibits the sulfides from elongating during hot working. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Mg is contained, the above effect can be obtained to a certain extent. However, if the Mg content exceeds 0.010%, the above effect is saturated. Therefore, the Mg content is 0 to 0.010%, and if contained, it is 0.010% or less. The preferable lower limit of the Mg content is 0.001%, and more preferably 0.002%. The preferable upper limit of the Mg content is 0.009%, and more preferably 0.008%.

[0065] Rare earth elements: 0.0100% or less Rare earth elements (REM) are optional elements and may not be contained. That is, the REM content may be 0%. When contained, that is, when the REM content is more than 0%, REM modifies sulfides in the steel material and inhibits the sulfides from elongating during hot working. As a result, the bending fatigue strength of the carburized steel part is increased. Even if even a small amount of REM is contained, the above effect can be obtained to some extent. However, if the REM content exceeds 0.0100%, the formation of coarse oxides is promoted even if the contents of other elements are within the range of this embodiment. In this case, the bending fatigue strength of the carburized steel part is reduced. Therefore, the REM content is 0 to 0.0100%, and when contained, it is 0.0100% or less. The preferable lower limit of the REM content is 0.0001%, more preferably 0.0010%, and more preferably 0.0020%. The preferable upper limit of the REM content is 0.0098%, and more preferably 0.0097%.

[0066] The steel material of the present embodiment may further contain one or more elements selected from the group consisting of Te, Bi, Pb, Sn, and Sb in place of a portion of Fe. These elements are optional elements, and all of them improve the machinability of the steel material.

[0067] Te: 0.100% or less Tellurium (Te) is an optional element and may not be contained. That is, the Te content may be 0%. When it is contained, that is, when the Te content is more than 0%, Te enhances the machinability of the steel material. If even a small amount of Te is contained, the above effect can be obtained to some extent. However, if the Te content exceeds 0.100%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Te content is 0 to 0.100%, and when it is contained, it is 0.100% or less. The preferred lower limit of the Te content is 0.001%, and more preferably 0.002%. The preferred upper limit of the Te content is 0.095%, and more preferably 0.090%.

[0068] Bi:0.500% or less Bismuth (Bi) is an optional element and may not be contained. That is, the Bi content may be 0%. When it is contained, that is, when the Bi content is more than 0%, Bi enhances the machinability of the steel material. If even a small amount of Bi is contained, the above effect can be obtained to some extent. However, if the Bi content exceeds 0.500%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Bi content is 0 to 0.500%, and if it is contained, it is 0.500% or less. The preferred lower limit of the Bi content is 0.001%, more preferably 0.005%, and more preferably 0.010%. The preferred upper limit of the Bi content is 0.450%, more preferably 0.400%, more preferably 0.350%, and more preferably 0.300%.

[0069] Pb: 0.09% or less Lead (Pb) is an optional element and may not be contained. That is, the Pb content may be 0%. When it is contained, that is, when the Pb content is more than 0%, Pb enhances the machinability of the steel material. If even a small amount of Pb is contained, the above effect can be obtained to some extent. However, if the Pb content exceeds 0.09%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Pb content is 0 to 0.09%, and if it is contained, it is 0.09% or less. The preferable lower limit of the Pb content is 0.01%, and more preferably 0.02%. The preferable upper limit of the Pb content is 0.08%, and more preferably 0.07%.

[0070] Sn: 0.015% or less Tin (Sn) is an optional element and may not be contained. In other words, the Sn content may be 0%. When it is contained, that is, when the Sn content is more than 0%, Sn enhances the machinability of the steel material. If even a small amount of Sn is contained, the above effect can be obtained to some extent. However, if the Sn content exceeds 0.015%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Sn content is 0 to 0.015%, and when it is contained, it is 0.015% or less. The preferable lower limit of the Sn content is 0.001%, and more preferably 0.005%. The preferable upper limit of the Sn content is 0.013%, and more preferably 0.010%.

[0071] Sb: 0.006% or less Antimony (Sb) is an optional element and may not be contained. In other words, the Sb content may be 0%. When it is contained, that is, when the Sb content is more than 0%, Sb enhances the machinability of the steel material. If even a small amount of Sb is contained, the above effect can be obtained to some extent. However, if the Sb content exceeds 0.006%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Sb content is 0 to 0.006%, and when it is contained, it is 0.006% or less. The preferable lower limit of the Sb content is 0.001%, and more preferably 0.002%. The preferable upper limit of the Sb content is 0.005%.

[0072] [Regarding formulas (1) to (4)] The chemical composition of the steel material of this embodiment further satisfies formulas (1) to (4), on the premise that the content of each element is within the range of this embodiment described above. 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn×Ni≦0.05 (2) 1.7≦Al / N≦2.4 (3) 22≦Mn / S≦65 (4) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (4). Each formula will be explained below.

[0073] [Regarding formula (1)] F1 is defined as (2Mn + 5Cr + Mo) / Si. F1 is an index showing the ability of cementite to form on the surface layer of steel during the vacuum carburizing process in the manufacturing process of producing carburized steel parts using steel as a raw material.

[0074] In the vacuum carburizing process, a carburizing step and a diffusion step are performed once each in a vacuum or under reduced pressure, or the carburizing step and the diffusion step are alternately repeated multiple times. In the carburizing process, a hydrocarbon-based gas is introduced to form an appropriate amount of cementite on the surface layer of the steel material. Then, in the diffusion process, the introduction of the hydrocarbon-based gas is stopped. Therefore, in the diffusion process, the cementite is decomposed, and the carbon concentration in the surface layer of the steel material increases due to the decomposition of the cementite. As a result, in the diffusion process of the vacuum carburizing process, the gradient of the carbon concentration in the austenite in the surface layer becomes larger compared to the diffusion process of the gas carburizing process, and the amount of C penetrating into the inside of the steel material can be increased. As described above, in the diffusion process of the vacuum carburizing process, no hydrocarbon-based gas is introduced, and the cementite formed on the surface layer of the steel material in the previous carburizing process is used as a carbon (C) supply source to diffuse and penetrate C into the inside of the steel material. As a result, the vacuum carburizing process can form a hardened layer in a short time compared to the gas carburizing process. The vacuum carburizing process is further performed under vacuum or reduced pressure. Therefore, a grain boundary oxide layer is unlikely to form on the surface layer of the steel material, and therefore the content of elements that easily form oxides, such as Si, Cr, and Mn, in the chemical composition of the steel material can be increased.

[0075] In the chemical composition of the steel material of this embodiment, Mn, Cr, and Mo all have high affinity with C, and thus tend to form cementite and alloy carbides (hereinafter, cementite, etc.) in the surface layer of the steel material in the carburizing step of the vacuum carburizing treatment. On the other hand, Si has low affinity with C, and thus tends to form cementite, etc. in the surface layer of the steel material in the carburizing step of the vacuum carburizing treatment. Therefore, in the chemical composition of the steel material of this embodiment, on the premise that the content of each element is within the range of this embodiment, by appropriately adjusting the contents of Mn, Cr, Mo, and Si, the amount of cementite, etc. in the surface layer of the steel material in the carburizing step of the vacuum carburizing treatment can be adjusted to an appropriate range.

[0076] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, when F1 is less than 2.5, the Si content is excessively high relative to the contents of Mn, Cr, and Mo. In this case, cementite and the like are unlikely to be formed in the surface layer of the steel material in the carburizing step of the vacuum carburizing treatment. Therefore, the gradient of the carbon concentration in the austenite becomes small in the diffusion step. As a result, the penetration and diffusion of C into the inside of the steel material becomes insufficient in the vacuum carburizing treatment. As a result, the hardness of the surface layer of the carburized steel part decreases, and the surface fatigue strength (pitting characteristics) decreases.

[0077] On the other hand, in the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, when F1 exceeds 7.5, the contents of Mn, Cr, and Mo are excessively high relative to the Si content. In this case, cementite and the like are formed in an excessively large amount on the surface layer of the steel material in the carburizing process of the vacuum carburizing treatment. As a result, although the cementite and the like are decomposed to a certain extent during the diffusion process, some of the coarse cementite and the like remain without being decomposed. Therefore, coarse cementite and the like may remain in the carburized steel part. In this case, the coarse cementite and the like become the starting point of cracks, and the bending fatigue strength of the carburized steel part decreases.

[0078] If F1 is 2.5 to 7.5, the Si content relative to the Mn, Cr, and Mo contents is in an appropriate range. Therefore, an appropriate amount of C penetrates into the steel material in the carburizing step of the vacuum carburizing treatment. As a result, on the premise that the content of each element in the chemical composition is within the range of this embodiment and formulas (2), (3), and (4) are satisfied, a carburized steel part manufactured using the steel material as a raw material has high bending fatigue strength and high surface fatigue strength.

[0079] The preferred lower limit of F1 is 2.6, more preferably 2.8, more preferably 3.0, more preferably 3.5, and more preferably 4.0. The preferred upper limit of F1 is 7.4, more preferably 7.3, more preferably 7.2, more preferably 7.0, and more preferably 6.8. F1 is a value obtained by rounding off the first decimal place of the value obtained by calculation.

[0080] [Regarding formula (2)] F2 is defined as Mn × Ni. F2 is an index related to the amount of retained austenite in the steel surface layer. Mn and Ni are austenite stabilizing elements, and both of them excessively increase the amount of retained austenite in the steel surface layer after carburizing. Therefore, if the content of these elements is excessively high, sufficient bending fatigue strength cannot be obtained in carburized steel parts.

[0081] In the chemical composition of the steel material of this embodiment, if F2 exceeds 0.05, the amount of retained austenite in the surface layer of the steel material after carburizing treatment increases excessively, assuming that the content of each element is within the range of this embodiment. In this case, sufficient bending fatigue strength is not obtained in the carburized steel part. If F2 is 0.05 or less, the Mn content and Ni content are kept within appropriate ranges. As a result, assuming that the content of each element in the chemical composition is within the range of this embodiment and satisfies formulas (1), (3) and (4), a carburized steel part manufactured using the steel material as a material can obtain high bending fatigue strength.

[0082] The upper limit of F2 is preferably 0.04, more preferably 0.03, more preferably 0.02, and even more preferably 0.01. There is no particular limit to the lower limit of F2. F2 may be 0. Note that F2 is a value obtained by rounding off the second decimal place of the value obtained by calculation.

[0083] [Regarding formula (3)] F3 is defined as F3=Al / N. F3 is an index related to Al inclusions and AlN precipitates, which affect bending fatigue strength. Al inclusions become the starting points of cracks during bending fatigue of carburized steel parts. Furthermore, coarse AlN (precipitates) also become the starting points of cracks during bending fatigue of carburized steel parts. Therefore, it is preferable to suppress the formation of Al inclusions and coarse AlN (precipitates) as much as possible.

[0084] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F3 is less than 1.7, the Al content is excessively high relative to the N content. In this case, the amount of Al inclusions in the steel material becomes excessively large. As a result, the bending fatigue strength of the carburized steel part decreases.

[0085] On the other hand, in the chemical composition of the steel material of this embodiment, if F3 exceeds 2.4, assuming that the content of each element is within the range of this embodiment, the N content is excessively higher than the Al content. In this case, the amount of coarse AlN (precipitates) in the steel material becomes excessively large. Therefore, in this case as well, the bending fatigue strength of the carburized steel part decreases.

[0086] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F3 is 1.7 to 2.4, the formation of Al inclusions in the steel material can be sufficiently suppressed, and the formation of coarse AlN (precipitates) can be sufficiently suppressed. Therefore, assuming that formulas (1), (2), and (4) are satisfied, the bending fatigue strength of the carburized steel part can be increased.

[0087] The lower limit of F3 is preferably 1.8, more preferably 1.9, and even more preferably 2.0. The upper limit of F3 is preferably 2.3, more preferably 2.2, and even more preferably 2.1. Note that F3 is a value obtained by rounding off the first decimal place of the value obtained by calculation.

[0088] [Regarding formula (4)] It is defined as F4=Mn / S. F4 is an index related to MnS, which affects bending fatigue strength. MnS improves the machinability of steel materials. However, coarse MnS can be the starting point of cracks during bending fatigue of carburized steel parts. Therefore, if an excessive amount of coarse MnS is formed, the bending fatigue strength of the carburized steel parts will decrease.

[0089] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F4 is less than 22, the S content is excessively high relative to the Mn content in the steel material. In this case, excessively large coarse MnS is formed. As a result, the bending fatigue strength of the carburized steel part manufactured using the steel material as a material is reduced. Furthermore, excessive FeS is formed at the grain boundaries. As a result, the hot workability of the steel material is reduced.

[0090] On the other hand, in the chemical composition of the steel material of this embodiment, if F4 exceeds 65, assuming that the content of each element is within the range of this embodiment, the Mn content is excessively high relative to the S content in the steel material. In this case, Mn segregates near the central axis of the steel material. Therefore, in this central segregation portion, an excessive amount of coarse MnS is formed. As a result, the bending fatigue strength of the carburized steel part manufactured using the steel material as a material is reduced.

[0091] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F4 is 22 to 65, the relationship between the Mn content and the S content is appropriate. Therefore, it is possible to suppress the excessive generation of coarse MnS. As a result, sufficient bending fatigue strength is obtained in the carburized steel part manufactured using the steel material as a material.

[0092] The preferred lower limit of F4 is 24, more preferably 26, more preferably 28, more preferably 30, more preferably 32, and more preferably 34. The preferred upper limit of F4 is 63, more preferably 61, more preferably 59, more preferably 57, more preferably 55, and more preferably 53. F4 is a value obtained by rounding off the first decimal place of the value obtained by calculation.

[0093] [About the microstructure of steel] The microstructure of the steel material of this embodiment is not particularly limited. The objective of the steel material of this embodiment is to obtain high bending fatigue strength and high surface fatigue strength in a carburized steel part manufactured using the steel material as a material. In the manufacturing process for manufacturing a carburized steel part using the steel material as a material, for example, a vacuum carburization process is performed on the steel material, as described below. In the vacuum carburization process, the steel material is subjected to A c3 Since the steel is heated to a temperature equal to or higher than the transformation point temperature, the microstructure of the steel is reset. Therefore, the microstructure of the steel, which is the raw material for the carburized steel part, is not particularly limited. The steel of this embodiment has the content of each element in the chemical composition within the above-mentioned range, and further satisfies formulas (1) to (4). Therefore, when a carburized steel part is manufactured by carrying out a vacuum carburizing process using the steel of this embodiment as the raw material, the carburized steel part can obtain high bending fatigue strength and high surface fatigue strength (pitting characteristics).

[0094] [Use of the steel material according to this embodiment] The steel material of this embodiment is suitable as a material for carburized steel parts manufactured by vacuum carburizing. In particular, it is suitable as a material for carburized steel parts that require bending fatigue strength and surface fatigue strength (pitting characteristics), such as gears used in mechanical products such as automobiles and construction vehicles. The steel material of this embodiment can also be used as a material for carburized steel parts manufactured by gas carburizing.

[0095] [Method of manufacturing steel material according to this embodiment] An example of a method for manufacturing the steel material of this embodiment will be described. The method for manufacturing the steel material described below is one example for manufacturing the steel material of this embodiment. Therefore, the steel material having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the steel material of this embodiment.

[0096] An example of the method for producing a steel material according to the present embodiment includes a step of preparing a material (a material preparation step) and a step of producing a steel material by hot working the material (a hot working step). Each step will be described below.

[0097] [Material preparation process] In the material preparation step, a material for the steel material of this embodiment is prepared. Specifically, molten steel is produced in which the content of each element in the chemical composition is within the range of this embodiment and satisfies formulas (1) to (4). The refining method is not particularly limited, and a well-known method may be used. For example, molten iron produced by a well-known method is refined in a converter (primary refining). The molten steel tapped from the converter is subjected to well-known secondary refining. In the secondary refining, alloy elements are added to adjust the composition, and molten steel is produced in which the content of each element is within the range of this embodiment and has a chemical composition that satisfies formulas (1) to (4).

[0098] The molten steel produced by the above-mentioned refining method is used to produce a material by a known casting method. For example, an ingot is produced by an ingot casting method using the molten steel. Also, a bloom may be produced by a continuous casting method using the molten steel. By the above-mentioned method, a material (ingot or bloom) is produced.

[0099] [Hot processing process] In the hot working process, hot working is performed on the material (ingot or bloom) prepared in the material preparation process to manufacture the steel material (steel bar) of this embodiment. The hot working method may be hot forging or hot rolling. In the following explanation, the case where the hot working is hot rolling will be explained. In this case, the hot working process includes, for example, a blooming process and a finish rolling process.

[0100] [Bulking rolling process] In the blooming process, the material is hot rolled to produce a billet. Specifically, in the blooming process, the material is hot rolled (blooming) by a blooming mill to produce a billet. If a continuous rolling mill is disposed downstream of the blooming mill, the billet after blooming may be further hot rolled by the continuous rolling mill to produce a smaller billet. The heating temperature in the blooming process may be within a known range. The heating temperature is, for example, 1000 to 1300°C.

[0101] [Finish rolling process] In the finish rolling process, the billet produced in the blooming process is hot-rolled using a continuous rolling mill to produce a steel bar. A known temperature is sufficient for the heating temperature in the finish rolling process. The heating temperature is, for example, 900 to 1250°C. The steel after hot rolling is cooled to room temperature. The cooling method is not particularly limited, but is, for example, natural cooling.

[0102] The steel material of this embodiment is manufactured by the above manufacturing method. Note that the above manufacturing method is one example of a manufacturing method for manufacturing the steel material of this embodiment. Therefore, the steel material of this embodiment may be manufactured by a method other than the above manufacturing method. In other words, the manufacturing method is not limited as long as the content of each element in the chemical composition is within the range of this embodiment and the steel material satisfies formulas (1) to (4).

[0103] In the above-mentioned example of the manufacturing method, the hot working step is carried out after the material preparation step. However, in the manufacturing method of the steel material of the present embodiment, the hot working step does not have to be carried out after the material preparation step. In other words, the steel material of the present embodiment may be a cast material (ingot, bloom, or billet).

[0104] In addition, the steel material after the material preparation process or the steel material after the hot working process may be subjected to a known normalizing treatment and / or a known spheroidizing annealing. In the spheroidizing annealing, for example, the annealing temperature is set to 720 to 780°C, and the holding time at the annealing temperature is set to 3 to 8 hours. Furthermore, the cooling time from the annealing temperature to 600°C is set to 4 hours or more (8 hours or less). Then, the steel material is allowed to cool.

[0105] [Composition of carburized steel parts] The carburized steel part of this embodiment is manufactured by performing vacuum carburization (vacuum carburization or vacuum carbonitriding) on ​​the steel material of this embodiment described above. The carburized steel part is a machine part, such as a gear, used in, for example, automobiles and construction vehicles.

[0106] The carburized steel part of this embodiment comprises a hardened layer and a core part located inside the hardened layer. The hardened layer is a layer hardened by the penetration and diffusion of C by vacuum carburization. Specifically, when vacuum carburization is performed, the hardened layer corresponds to the carburized layer, and when vacuum carbonitriding is performed, the hardened layer corresponds to the carbonitrided layer. The core part is located inside the hardened layer and is an area that is not affected by the penetration and diffusion of C by vacuum carburization. It is a technical matter well known to those skilled in the art that the hardened layer and the core part can be distinguished by well-known microstructural observation.

[0107] [About the core] The chemical composition of the core of the carburized steel part of this embodiment is the same as that of the steel material of this embodiment described above. Specifically, the chemical composition of the core of the carburized steel part of this embodiment contains, by mass%, C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P: 0.030% or less, S: 0.050% or less, Ni: 0.01-0.20%, Cr: 0.65-1.50%, Mo: 0.01-0.60%, Al: 0.045% or less, and N: 0.0250% or less, with the balance being Fe and impurities, and satisfies formulas (1) to (4). 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn×Ni≦0.05 (2) 1.7≦Al / N≦2.4 (3) 22≦Mn / S≦65 (4) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (4).

[0108] The chemical composition of the core may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of V: ​​0.50% or less, Nb: 0.030% or less, Ti: 0.200% or less, Cu: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, and B: 0.0010% or less.

[0109] The chemical composition of the core portion may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of Ca: 0.0015% or less, Mg: 0.010% or less, and rare earth elements: 0.0100% or less.

[0110] The chemical composition of the core may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of Te: 0.100% or less, Bi: 0.500% or less, Pb: 0.09% or less, Sn: 0.015% or less, and Sb: 0.006% or less.

[0111] [About the hardened layer] The composition of the hardened layer is as follows: (1) The carbon concentration in the region from the surface to a depth of 50 μm of the carburized steel component is 0.60% or more by mass. (2) The microstructure of the carburized steel part at a depth of 20 μm from the surface consists of martensite or consists of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. Each component will be described below.

[0112] [Surface carbon concentration] The area from the surface of the carburized steel part to a depth of 50 μm (hereinafter referred to as the surface region) is included in the hardened layer. The C concentration in the surface region is 0.60% or more by mass. The C concentration in the hardened layer is higher than the C concentration in the core. If the C concentration in the surface region is 0.60% or more by mass, the hardness of the hardened layer is sufficiently high. Therefore, the carburized steel part can obtain sufficient surface fatigue strength and sufficient bending fatigue strength.

[0113] The lower limit of the C concentration in the surface region is preferably 0.65%, more preferably 0.70%, and even more preferably 0.75%. The upper limit of the C concentration in the surface region is not particularly limited. The upper limit of the C concentration in the surface region is preferably 1.30%, for example, more preferably 1.20%, and even more preferably 1.10%.

[0114] [Method for measuring surface carbon concentration] The carbon concentration in the surface region can be measured by the following method. Cutting is performed from the surface of the carburized steel part to a depth of 50 μm, and chips from the surface region to a depth of 50 μm are collected. Chemical analysis is performed using the collected chips. Specifically, the well-known high-frequency combustion method (combustion-infrared absorption method) is performed on the collected chips to obtain the carbon concentration. Specifically, the above-mentioned chips are burned by high-frequency induction heating in an oxygen stream, and the generated carbon dioxide and carbon monoxide are detected to determine the carbon concentration (mass %). The obtained carbon concentration (mass %) is defined as the carbon concentration (mass %) in the region from the surface of the carburized steel part to a depth of 50 μm (surface region).

[0115] [Microstructure of the hardened layer] The hardened layer includes a depth of 20 μm from the surface of the carburized steel part. The microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. In other words, when the microstructure is made of martensite and retained austenite, the volume fraction of the retained austenite is 40% or less. It is technically common knowledge that the microstructure in the hardened layer is mainly martensite.

[0116] If the volume fraction of the retained austenite at a depth of 20 μm from the surface of the carburized steel part exceeds 40%, the hardness of the hardened layer is too low. In this case, the bending fatigue strength of the carburized steel part is reduced. If the volume fraction of the retained austenite at a depth of 20 μm from the surface of the carburized steel part is 0-40%, the hardened layer has sufficient hardness. Therefore, the bending fatigue strength of the carburized steel part is increased. The preferred upper limit of the volume fraction of the retained austenite at a depth of 20 μm from the surface of the carburized steel part is 35%, more preferably 30%, and even more preferably 28%. The lower the volume fraction of the retained austenite, the better. However, it is difficult to reduce the retained austenite to 0%, and the manufacturing cost is also high. Therefore, in consideration of industrial production, the preferred lower limit of the retained austenite is more than 0%, and even more preferably 1%.

[0117] [Method for measuring volume fraction of retained austenite] The volume fraction of retained austenite is measured by the following method. A carburized steel component is electrolytically polished to a depth of 20 μm from the surface, and a portion 20 μm deep from the surface is exposed. An X-ray diffraction device is used to irradiate any position on the exposed surface with X-rays to measure the volume fraction (%) of retained austenite. The volume fraction of retained austenite is calculated from the ratio (integral intensity ratio) of the integrated intensity of the (211) bcc diffraction peak obtained by X-ray diffraction to the integrated intensity of the (220) fcc diffraction peak. Specifically, the volume fraction (%) of retained austenite can be calculated from the following formula, where the integrated intensity of (211) bcc (α phase) is Iα and the integrated intensity of (220) fcc (γ phase) is Iγ. Volume fraction of retained austenite = Iγ / (RIα+Iγ) Here, R = 0.36746.

[0118] The carburized steel part having the above configuration has the content of each element in the chemical composition of the core within the above-mentioned range, and satisfies formulas (1) to (4). Furthermore, the C concentration in the region from the surface of the carburized steel part to a depth of 50 μm (surface layer region) is 0.60% or more, and the microstructure at a depth of 20 μm from the surface of the carburized steel part consists of martensite or martensite and retained austenite, with the volume fraction of retained austenite being 0 to 40%. Therefore, the carburized steel part of this embodiment has high bending fatigue strength and high surface fatigue strength.

[0119] [Manufacturing method for carburized steel parts] An example of a manufacturing method for the carburized steel part of this embodiment will be described. The manufacturing method for the carburized steel part described below is one example for manufacturing the carburized steel part of this embodiment. Therefore, the carburized steel part having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a manufacturing method for the carburized steel part of this embodiment.

[0120] The carburized steel part is subjected to a hot working process or a cold working process, a cutting process, and a heat treatment process. Either the hot working process or the cold working process is performed.

[0121] [Hot processing process] When the hot working step is carried out, hot working is carried out on the steel material of this embodiment. The hot working is, for example, well-known hot forging. The heating temperature in the hot working step is, for example, 1000 to 1300°C. After the hot working, the steel material is naturally cooled (air-cooled).

[0122] [Cold working process] When the cold working step is performed, the steel material of the present embodiment is subjected to a well-known spheroidizing annealing, and then cold working is performed. The conditions of the cold working are not particularly limited.

[0123] [Cutting process] In the cutting process, the steel material after the hot working process is cut to produce an intermediate product of a predetermined shape. By performing cutting, it is possible to give the carburized steel part a precise shape that would be difficult to achieve by the hot working process or cold working process alone.

[0124] [Heat treatment process] The intermediate product after the cutting process is subjected to a heat treatment. Here, the "heat treatment" includes a well-known vacuum carburizing process, a well-known quenching process, and a well-known tempering process. In the vacuum carburizing process, it is a well-known technical matter for those skilled in the art to adjust the C concentration and microstructure of the hardened layer of the carburized steel part by appropriately adjusting well-known conditions. The well-known vacuum carburizing process, quenching process, and tempering process will be described below.

[0125] [Vacuum carburizing process] Fig. 1 is a diagram showing an example of a heat pattern for the vacuum carburizing process S10 and the quenching process S20. The vacuum carburizing process S10 includes a heating process S0, a carburizing process S1, and a diffusion process S2. In the heat pattern of Fig. 1, the carburizing process S1 is followed by the diffusion process S2, and the carburizing process S1 and the diffusion process S2 are then repeatedly performed. In this way, in the vacuum carburizing process S10, the carburizing process S1 and the diffusion process S2 may be repeated multiple times, or the carburizing process S1 and the diffusion process S2 may be performed once each. The carburizing process S1 and the diffusion process S2 may be repeated three or more times.

[0126] In the heating step S0, the intermediate product loaded into the furnace is heated to the carburizing temperature Tc. The carburizing temperature Tc in the heating step S0 is, for example, 900 to 1100° C. In the heating step S0, the inside of the furnace is further evacuated or reduced in pressure. For example, the inside of the furnace is reduced in pressure to 1 kPa or less.

[0127] In the carburizing step S1, a hydrocarbon gas is introduced into a furnace in a vacuum or under reduced pressure, and the intermediate product is held at the carburizing temperature Tc for a predetermined time (holding time t1) to perform the carburizing treatment. The gas introduced in the carburizing step S1 is not particularly limited as long as it is a hydrocarbon gas, and for example, acetylene or propane is used. The holding time t1 at the carburizing temperature Tc is not particularly limited, and is, for example, 5 to 120 minutes. By carrying out carburizing in a vacuum or under reduced pressure, the C concentration penetrating into the steel surface layer can be increased compared to the case of gas carburizing treatment.

[0128] In the diffusion step S2, the carburizing temperature Tc is maintained for a predetermined time (retention time t2) without introducing a hydrocarbon gas into the furnace. The pressure in the furnace in the diffusion step may be the same as that in the carburizing step S1, or may be reduced in pressure (e.g., 100 Pa or less) compared to the carburizing step S1 in order to remove residual gas in the carburizing step S1. The retention time t2 at the carburizing temperature Tc is not particularly limited, but is, for example, 5 to 120 minutes.

[0129] In the vacuum carburizing process S10, in the carburizing step S1, C is caused to penetrate into the surface layer of the steel material, forming cementite and the like in the surface layer. Then, in the diffusion step S2, the cementite and the like in the surface layer are decomposed and the C in the surface layer is diffused into the interior. By repeating the combination of the carburizing step S1 and the diffusion step S2 once or a plurality of times under vacuum or reduced pressure, a large amount of C can penetrate and diffuse into the steel material in a short time compared to gas carburizing.

[0130] [Quenching process] The intermediate product after the vacuum carburizing process S10 is subjected to a quenching process S20. In the quenching process S20, the intermediate product after the vacuum carburizing process S10 is r3 After being held at a quenching temperature equal to or higher than the quenching temperature Ts, the intermediate product is quenched and quenched. The holding time t3 at the quenching temperature Ts is not particularly limited, but is, for example, 15 to 60 minutes. The quenching temperature Ts is preferably lower than the carburizing temperature Tc. The cooling method in the quenching process is oil cooling or water cooling. Specifically, the intermediate product held at the quenching temperature is immersed in a cooling bath containing oil or water as a cooling medium to be quenched.

[0131] [Tempering process] The intermediate product after the quenching process is subjected to a known tempering process. The tempering temperature is, for example, 100 to 200° C. The holding time at the tempering temperature is, for example, 60 to 150 minutes.

[0132] [Other processes] The method for manufacturing the carburized steel part of this embodiment may further include a shot peening step and a finish grinding step, which are optional steps.

[0133] [Shot peening process] The shot peening process is an optional process and does not have to be performed. If performed, the shot peening process is performed on the intermediate product after the heat treatment process. By performing the shot peening process, the retained austenite in the hardened layer of the carburized steel part undergoes processing-induced transformation to martensite. As a result, the volume fraction of the retained austenite in the hardened layer decreases. For example, the shot peening process preferably uses a cut wire or shot grains with a diameter of 1.0 mm or less, has an arc height of 0.3 mmA or more, and has a coverage of 300% or more.

[0134] [Finishing grinding process] The finish grinding process is an optional process and does not have to be performed. If performed, the finish grinding process is performed on the intermediate product after the heat treatment process or the shot peening process to adjust the surface properties.

[0135] The carburized steel part of this embodiment can be manufactured by the above manufacturing steps. The above manufacturing method is one example of a manufacturing method for manufacturing the carburized steel part of this embodiment. Therefore, the carburized steel part of this embodiment may be manufactured by a method other than the above manufacturing method. In other words, the manufacturing method of the carburized steel part is not particularly limited as long as the content of each element in the chemical composition of the core of the carburized steel part is within the range of this embodiment and satisfies formulas (1) to (4), the C concentration in the region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more, the microstructure at a depth of 20 μm from the surface of the carburized steel part consists of martensite or consists of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. EXAMPLES

[0136] The effects of the steel material and carburized steel part of this embodiment will be explained in more detail below with reference to examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effects of the steel material and carburized steel part of this embodiment. Therefore, the steel material and carburized steel part of this embodiment are not limited to this one example of conditions.

[0137] [Steel manufacturing] Molten steel having the chemical composition shown in Table 1 was produced.

[0138] [Table 1]

[0139] Ingots were produced by the ingot casting method using the molten steel in Table 1. The cross section perpendicular to the longitudinal direction of the ingot was a rectangle of 180 mm x 180 mm. The produced ingot was allowed to cool to room temperature.

[0140] The ingot was heated at 1200°C for 2 hours. The heated ingot was subjected to hot working (hot forging) to produce steel material (steel bar) having a diameter of 40 mm and a length of 1000 mm. The hot worked steel material was allowed to cool to room temperature. The steel material after cooling was subjected to normalizing treatment. The treatment temperature in the normalizing treatment was 925°C, and the holding time at the treatment temperature was 90 minutes. After the holding time had elapsed, the steel material was allowed to cool. The cooling rate of the steel material during cooling was 0.3 to 0.9°C / sec. Through the above steps, the steel material (steel bar) of each test number was produced.

[0141] The steel material with test number 46 had a chemical composition equivalent to SCr420 as specified in JIS G 4805 (2019). The steel material with test number 46 was designated as the "reference steel material."

[0142] [Evaluation test] [Manufacturing of carburized steel part test pieces] The steel materials produced for each test number were used to prepare the following three types of carburized steel part test pieces for each test number.

[0143] (1) Small roller test piece Figure 2 shows a side view of the small roller test piece produced in this example. The numbers in Figure 2 indicate dimensions (unit: mm). "φ" in Figure 2 means diameter. The inverted triangle symbol in Figure 2 means the "finishing symbol" indicating the surface roughness described in Table 1 of JIS B 0601 (1982). The "G" attached to the finishing symbol means the abbreviation of the processing method indicating the grinding specified in JIS B 0122 (1978). The small roller test piece is a test piece for measuring surface fatigue strength. Multiple small roller test pieces were prepared for each test number.

[0144] (2) Rotating bending fatigue test piece Figure 3 shows a side view of the rotating bending fatigue test piece produced in this example. The numbers in Figure 3 indicate dimensions (unit: mm). "φ" in Figure 3 means diameter. "R" in Figure 3 means radius of curvature. The rotating bending fatigue test piece is a test piece for measuring rotating bending fatigue strength.

[0145] (3) Test pieces for hardened layer investigation Two test pieces were prepared for each test number to investigate the hardened layer. The test pieces were cylindrical, measuring 26 mm in diameter and 100 mm in length.

[0146] Test pieces for each carburized steel component were prepared in the following manner.

[0147] [Small roller test piece] The steel material of each test number was machined to produce a rough test piece having the rough shape of the small roller test piece. The rough test piece was subjected to one of the following heat treatments, Pattern 1 to Pattern 3. The heat treatment patterns (1 to 3) performed for each test number are shown in the "Heat Treatment Pattern" column of Table 2. Note that "-" in the "Heat Treatment Pattern" column means that no heat treatment was performed.

[0148] (Pattern 1) The following vacuum carburizing process was carried out. The carburizing process involved introducing acetylene gas at a furnace pressure of 100 Pa or less. The temperature in the carburizing process was set to 930°C and the holding time was 80 minutes. After the carburizing process, a diffusion process was carried out. In the diffusion process, the introduction of acetylene gas was stopped and the furnace pressure was set to 10 Pa or less. The temperature in the diffusion process was set to 930°C and the holding time was 20 minutes. After the diffusion process, a quenching process was carried out. In the quenching process, the temperature was set to 900°C and the holding time was 30 minutes. After the holding time had elapsed, the material was oil-cooled using 60°C oil. After the quenching process, a tempering process was carried out. In the tempering process, the temperature was set to 180°C and the holding time was 120 minutes.

[0149] (Pattern 2) The following vacuum carburizing process was carried out. The carburizing process involved introducing acetylene gas at a furnace pressure of 100 Pa or less. The temperature in the carburizing process was set to 950°C and the holding time was set to 50 minutes. After the carburizing process, a diffusion process was carried out. In the diffusion process, the introduction of acetylene gas was stopped and the furnace pressure was set to 10 Pa or less. The temperature in the diffusion process was set to 950°C and the holding time was set to 15 minutes. After the diffusion process, a quenching process was carried out. In the quenching process, the temperature was set to 900°C and the holding time was set to 30 minutes. After the holding time had elapsed, the material was oil-cooled using 60°C oil. After the quenching process, a tempering process was carried out. In the tempering process, the temperature was set to 180°C and the holding time was set to 120 minutes.

[0150] (Pattern 3) The following vacuum carburizing process was carried out. The carburizing process involved introducing acetylene gas at a furnace pressure of 100 Pa or less. The temperature in the carburizing process was set to 970°C and the holding time was 15 minutes. After the carburizing process, a diffusion process was carried out. In the diffusion process, the introduction of acetylene gas was stopped and the furnace pressure was set to 10 Pa or less. The temperature in the diffusion process was set to 970°C and the holding time was 40 minutes. After the diffusion process, a quenching process was carried out. In the quenching process, the temperature was set to 900°C and the holding time was 30 minutes. After the holding time had elapsed, the material was oil-cooled using 60°C oil. After the quenching process, a tempering process was carried out. In the tempering process, the temperature was set to 180°C and the holding time was 120 minutes.

[0151] For test number 46 (reference steel), the following reference steel heat treatment pattern (known gas carburizing treatment) was applied to the rough test piece. Specifically, the test piece was held at 930°C for 180 minutes in an atmosphere with a carbon potential CP of 1.0% (carburizing process). Then, the carbon potential CP was set to 0.8% and the test piece was held at 930°C for 120 minutes (diffusion process). Then, the temperature was lowered to 870°C, and the test piece was held at 870°C for 30 minutes, and then oil-cooled in oil at 60°C (quenching process). The rough test piece after oil cooling was subjected to a tempering process. The tempering temperature was 180°C, and the holding time at the tempering temperature was 120 minutes.

[0152] After the heat treatment, the cylindrical part in the center of the rough test piece was ground to be finished into a cylindrical part with a diameter of 26 mm as shown in Figure 2. At this time, the surface of the cylindrical part with a diameter of 26 mm was finished so that the arithmetic mean roughness Ra was 0.6 to 0.8 μm and the maximum height Rz was 2.0 to 4.0 μm in accordance with JIS B 0601 (2001). The grinding depth was about 10 μm.

[0153] Furthermore, shot peening was performed on the rough test pieces of some of the test numbers (indicated as "Yes" in the "Shot Peening" column in Table 2). For the shot peening, a commercially available round cut wire with a diameter of 0.6 mm was used as the blast material. Furthermore, the arc height was 0.4 mmA, and the coverage was 300%. Shot peening was performed on the outer circumferential surface of the cylindrical part with a diameter of 26 mm shown in Figure 2. Shot peening was not performed on the rough test pieces of the remaining test numbers (indicated as "No" in the "Shot Peening" column in Table 2). Using the above manufacturing process, small roller test pieces of each test number were produced.

[0154] [Rotating bending fatigue test piece] The steel material of each test number was machined to produce a rough test piece for a rotating bending fatigue test piece. The rough test pieces were subjected to heat treatment according to any one of the above-mentioned patterns 1 to 3. The heat treatment pattern performed on the rough test pieces of each test number was as shown in Table 2. The rough test piece of test number 46 was subjected to heat treatment according to the above-mentioned reference steel heat treatment pattern. Shot peening was performed on the rough test pieces after heat treatment of some test numbers (listed as "Yes" in the "Shot Peening" column in Table 2). In the shot peening, commercially available high-hardness particles with a diameter of 0.5 mm and a hardness of 900 HV were used as the projectile. Furthermore, the arc height was set to 0.4 mmA, and the coverage was set to 300%. The rough test pieces of the remaining test numbers were not subjected to shot peening (listed as "No" in the "Shot Peening" column in Table 2).

[0155] After the shot peening treatment or the heat treatment, the surface of the crude test piece was machined to prepare a rotating bending fatigue test piece with the dimensions shown in Fig. 3. Note that no machining was performed to adjust the surface properties of the notch formed in the center position of the rotating bending fatigue test piece in the longitudinal direction. The rotating bending fatigue test piece was prepared by the above manufacturing process.

[0156] [Test piece for hardened layer investigation] The steel material of each test number was machined to prepare two cylindrical rough test pieces with a diameter of 26 mm and a length of 100 mm. The rough test pieces were subjected to heat treatment according to any one of the above-mentioned patterns 1 to 3. The heat treatment pattern performed on the rough test pieces of each test number was as shown in Table 2. Thereafter, similar to the small roller test piece, the outer peripheral surface of the rough test piece was ground to finish the outer peripheral surface. At this time, the outer peripheral surface of the rough test piece with a diameter of 26 mm was finished so that the arithmetic mean roughness Ra according to JIS B 0601 (2001) was 0.6 to 0.8 μm and the maximum height Rz was 2.0 to 4.0 μm. The grinding depth was about 10 μm.

[0157] Furthermore, shot peening was carried out on the crude test pieces of some of the test numbers (indicated as "Yes" in the "Shot Peening" column in Table 2). For shot peening, commercially available high-hardness particles with a diameter of 0.5 mm and a hardness of 900 HV were used as the projection material. Furthermore, the arc height was set to 0.4 mmA, and the coverage was set to 300%. Shot peening was not carried out on the crude test pieces of the remaining test numbers (indicated as "No" in the "Shot Peening" column in Table 2). Using the above manufacturing process, test pieces for investigating the hardened layer were produced.

[0158] [Manufacturing of large roller test pieces for twin-roller fatigue testing] Large roller test pieces used in twin-cylinder rolling fatigue tests to measure surface fatigue strength were manufactured in the following manner. Rough test pieces for large roller test pieces with the shape shown in Figure 4 were cut out from a cylindrical material with a diameter of 140 mm and a chemical composition equivalent to SUJ2 as specified in JIS G 4805 (2008). The numbers in Figure 4 indicate dimensions (unit: mm). The inverted triangle symbol in Figure 4 indicates the "finishing symbol" indicating the surface roughness described in Table 1 of JIS B 0601 (1982). The "G" attached to the finishing symbol indicates the abbreviation for the processing method indicating grinding as specified in JIS B 0122 (1978).

[0159] The cut rough test pieces were quenched. The quenching temperature was 870°C, and the holding time at the quenching temperature was 90 minutes. After the holding time had elapsed, the rough test pieces were quenched in oil at 60°C. The outer peripheral surface of the quenched rough test pieces was finished by cutting. The outer peripheral surface was finished so that the arithmetic mean roughness Ra was 0.6 to 0.8 μm and the maximum height Rz was 2.0 to 4.0 μm. Large roller test pieces were produced by the above manufacturing process.

[0160] [C concentration measurement test of hardened layer of carburized steel part specimen] Using the test pieces for hardened layer investigation of each test number, the carbon concentration in the region from the surface to a depth of 50 μm was measured by the following method. The test pieces for hardened layer investigation were turned to a depth of 50 μm from the surface, and chips were collected. Chemical analysis was performed using the collected chips. Specifically, the collected chips were dissolved in acid to obtain a solution. The well-known high-frequency combustion method (combustion-infrared absorption method) was performed on the obtained solution to obtain the carbon concentration. Specifically, the above-mentioned solution was burned by high-frequency induction heating in an oxygen stream, and the generated carbon dioxide was detected to obtain the carbon concentration (mass%). The obtained carbon concentration (mass%) was defined as the carbon concentration (mass%) in the region from the surface of the carburized steel part to a depth of 50 μm (surface region).

[0161] [Measurement test of retained austenite volume fraction in the hardened layer of carburized steel part specimens] Using the test pieces for hardened layer investigation of each test number, the volume fraction of retained austenite at a depth of 20 μm from the surface of the carburized steel part was determined by the following method. The carburized steel part was electrolytically polished to a depth of 20 μm from the surface, and the 20 μm depth from the surface was exposed. Using an X-ray diffractometer, an arbitrary position on the exposed surface was irradiated with X-rays to measure the volume fraction (%) of retained austenite. The volume fraction of retained austenite was calculated from the ratio (integral intensity ratio) of the integrated intensity of the diffraction peak of (211)bcc obtained by X-ray diffraction to the integrated intensity of the diffraction peak of (220)fcc. Specifically, the volume fraction (%) of retained austenite was calculated from the following formula, where the integrated intensity of (211)bcc (α phase) is Iα and the integrated intensity of (220)fcc (γ phase) is Iγ. Volume fraction of retained austenite = Iγ / (RIα+Iγ) Here, R = 0.36746.

[0162] [Surface fatigue strength measurement test (two-cylinder rolling fatigue test)] A twin-cylinder rolling fatigue test was carried out using the small roller test piece and the large roller test piece to determine the surface fatigue strength as follows. A RP201 manufactured by Komatsu Engineering Co., Ltd. was used as a test machine. As shown in FIG. 5, the cylindrical portion of the small roller test piece 10 with a diameter of 26 mm and the central position of the outer peripheral surface of the large roller test piece 20 (the outer peripheral portion with a diameter of 130 mm) were rolled while being in contact with each other. The contact pressure was 1800 to 3500 MPa in Hertzian contact pressure. The rotation speed of the small roller test piece 10 was 1500 rpm. The peripheral speed of the small roller test piece 10 was 123 m / min, and the peripheral speed of the large roller test piece 10 was 172 m / min. During the test, lubricating oil was supplied to the contact portion between the small roller test piece and the large roller test piece. The lubricating oil was automatic transmission oil, the oil temperature was 100° C., and the oil amount was 1.0 L / min. The number of repetitions in the test was 2.0×10 , which indicates the fatigue limit of general steel. 7 The small roller test piece was tested for 2.0×10 7The maximum surface pressure (MPa) reached in the test was taken as the fatigue limit of the small roller test piece. The occurrence of pitting was detected by a vibration meter attached to the test machine. After the occurrence of vibration, the rotation of both the small roller test piece and the large roller test piece was stopped, and the occurrence of pitting and the number of rotations were confirmed. In this embodiment, assuming application to gear parts, the fatigue limit of the small roller test piece made of steel (reference steel) satisfying the SCr420 standard of test number 46 was taken as the reference value. When the fatigue limit was 1.20 times or more that of the reference steel, it was judged to have excellent surface fatigue strength ("○" in the "surface fatigue strength" column in Table 2). On the other hand, when the fatigue limit was less than 1.20 times that of the reference steel, it was judged to have low surface fatigue strength ("×" in the "surface fatigue strength" column in Table 2).

[0163] [Rotating bending strength measurement test (rotating bending fatigue test)] Rotating bending fatigue test specimens were used to carry out rotating bending fatigue tests in accordance with the "Rotating bending fatigue test method for metallic materials" specified in JIS Z 2274 (1978). The tests were carried out at room temperature in an air atmosphere, with the rotation speed set to 3000 rpm. The number of repeated stress loads was 10 7 The maximum stress at which the steel did not break after the cycles was taken as the bending fatigue strength (MPa). If the obtained bending fatigue strength was 1.20 times or more the bending fatigue strength of the reference steel material, test number 46, it was judged to have excellent bending fatigue strength (marked with "○" in the "Bending fatigue strength" column in Table 2). On the other hand, if the obtained bending fatigue strength was less than 1.20 times the bending fatigue strength of the reference steel material, test number 46, it was judged to have low bending fatigue strength (marked with "×" in the "Bending fatigue strength" column in Table 2).

[0164] [Evaluation Results] The test results are shown in Table 2.

[0165] [Table 2]

[0166] Referring to Table 2, the contents of each element in the chemical composition of the steel materials of test numbers 1 to 26 were appropriate, and furthermore, F1 to F4 satisfied formulas (1) to (4). Therefore, in the carburized steel parts manufactured by vacuum carburizing, the C concentration in the region from the surface of the carburized steel part to a depth of 50 μm was 0.60% by mass or more, and the microstructure at a depth of 20 μm from the surface of the carburized steel part was composed of martensite and retained austenite, with the volume fraction of retained austenite being 40% or less. As a result, excellent bending fatigue strength and excellent surface fatigue strength were obtained.

[0167] On the other hand, in test number 27, the C content was low, and therefore the bending fatigue strength was low.

[0168] In test number 28, the Si content was too high. As a result, the C content in the surface layer was too low, and the contact fatigue strength was low.

[0169] In test number 29, the Si content was too low, which resulted in low contact fatigue strength.

[0170] In test number 30, the Mn content was too high. As a result, the bending fatigue strength was low. In addition, because the Mn content was too high, the volume fraction of retained austenite exceeded 40% in the microstructure at a depth of 20 μm from the surface of the carburized steel part.

[0171] In test number 31, the Mn content was too low, which resulted in low contact fatigue strength.

[0172] In test number 32, the P content was too high, which resulted in low bending fatigue strength.

[0173] In test number 33, the S content was too high, which resulted in low bending fatigue strength.

[0174] In test number 34, the Cr content was too high, which resulted in low bending fatigue strength.

[0175] In test number 35, the Cr content was too low, which resulted in low contact fatigue strength.

[0176] In test number 36, the Al content was too high, which resulted in low bending fatigue strength.

[0177] In test number 37, the N content was too high, which resulted in low bending fatigue strength.

[0178] In test number 38, the content of each element in the chemical composition of the steel was appropriate, but F1 exceeded the upper limit of formula (1). As a result, the bending fatigue strength was low.

[0179] In test number 39, the content of each element in the chemical composition of the steel was appropriate, but F1 was below the lower limit of formula (1). As a result, the contact fatigue strength was low.

[0180] In test number 40, the content of each element in the chemical composition of the steel was appropriate, but F3 exceeded the upper limit of formula (3). As a result, the bending fatigue strength was low.

[0181] In test number 41, the content of each element in the chemical composition of the steel was appropriate, but F3 was below the lower limit of formula (3). As a result, the bending fatigue strength was low.

[0182] In test number 42, the content of each element in the chemical composition of the steel was appropriate, but F4 exceeded the upper limit of formula (4). As a result, the bending fatigue strength was low.

[0183] In test number 43, the content of each element in the chemical composition of the steel was appropriate, but F4 was below the lower limit of formula (4). As a result, cracks occurred during hot forging. Therefore, the above evaluation tests were not performed on test number 43.

[0184] In test number 44, the Mo content was too low, and therefore the contact fatigue strength was too low.

[0185] In test number 45, the content of each element in the chemical composition of the steel was appropriate, but F2 exceeded the upper limit of formula (2). As a result, the volume fraction of retained austenite in the surface layer of the carburized steel part exceeded 40%, and the bending fatigue strength was low.

[0186] The above describes the embodiments of the present invention. However, the above-described embodiments are merely examples for carrying out the present invention. Therefore, the present invention is not limited to the above-described embodiments, and the above-described embodiments can be appropriately modified and carried out without departing from the spirit of the present invention.

Claims

1. Chemical composition in mass percent: C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P: 0.030% or less, S: 0.050% or less, Ni: 0.01 to 0.20%, Cr: 0.65-1.50%, Mo: 0.01 to 0.60%, Al: 0.045% or less, N: 0.0250% or less, V: 0-0.50%, Nb: 0 to 0.030%, Ti: 0-0.200%, Cu: 0 to 0.50%, W: 0-0.50%, Co: 0 to 0.50%, B: 0 to 0.0050%, Ca: 0-0.0015%, Mg: 0 to 0.010%, Rare earth elements: 0 to 0.0100%, Te: 0 to 0.100%, Bi: 0-0.500%, Pb: 0 to 0.09%, Sn: 0 to 0.015%, and Sb: 0 to 0.006%, The balance is Fe and impurities, and satisfies formulas (1) to (4). Steel material. 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn × Ni ≦ 0.03 (2) 1.9≦Al / N≦2.1 (3) 24≦Mn / S≦65 (4) Here, the content of the corresponding element in mass % is substituted for each element symbol in formulas (1) to (4).

2. The steel material according to claim 1, The chemical composition is, in place of a part of Fe, V: 0.01-0.50%, Nb: 0.001-0.030%, Ti: 0.001 to 0.200%, Cu: 0.01 to 0.50%, W: 0.01-0.50%, Co: 0.01 to 0.50%, and B: 0.0001 to 0.0010%, Contains one or more selected from the group consisting of Steel material.

3. The steel material according to claim 1 or 2, The chemical composition is, in place of a part of Fe, Ca: 0.0001-0.0015%, Mg: 0.001 to 0.010%, and Rare earth elements: 0.0001 to 0.0100%, Contains one or more selected from the group consisting of Steel material.

4. The steel material according to any one of claims 1 to 3, The chemical composition is, in place of a part of Fe, Te: 0.001 to 0.100%, Bi: 0.001-0.500%, Pb: 0.01-0.09%, Sn: 0.001 to 0.015%, and Sb: 0.001 to 0.006%, Contains one or more selected from the group consisting of Steel material.

5. A carburized steel part, A hardened layer; A core portion is provided inside the hardened layer, The chemical composition of the core is, in mass%, C: 0.10-0.35%, Si: 0.60-1.50%, Mn: 0.20-1.30%, P: 0.030% or less, S: 0.050% or less, Ni: 0.01 to 0.20%, Cr: 0.65-1.50%, Mo: 0.01 to 0.60%, Al: 0.045% or less, N: 0.0250% or less, V: 0-0.50%, Nb: 0 to 0.030%, Ti: 0-0.200%, Cu: 0 to 0.50%, W: 0-0.50%, Co: 0 to 0.50%, B: 0 to 0.0050%, Ca: 0-0.0015%, Mg: 0 to 0.010%, Rare earth elements: 0 to 0.0100%, Te: 0 to 0.100%, Bi: 0-0.500%, Pb: 0 to 0.09%, Sn: 0 to 0.015%, and Sb: 0 to 0.006%, and the balance being Fe and impurities, and satisfying formulas (1) to (4), The carbon concentration in a region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more by mass%, The microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. Carburized steel parts. 2.5≦(2Mn+5Cr+Mo) / Si≦7.5 (1) Mn × Ni ≦ 0.03 (2) 1.9≦Al / N≦2.1 (3) 24≦Mn / S≦65 (4) Here, the content of the corresponding element in mass % is substituted for each element symbol in formulas (1) to (4).

6. 6. A carburized steel component according to claim 5, The chemical composition of the core portion is, in place of a part of Fe, V: 0.01-0.50%, Nb: 0.001-0.030%, Ti: 0.001 to 0.200%, Cu: 0.01 to 0.50%, W: 0.01-0.50%, Co: 0.01 to 0.50%, and B: 0.0001 to 0.0010%, Contains one or more selected from the group consisting of Carburized steel parts.

7. A carburized steel part according to claim 5 or claim 6, The chemical composition of the core portion is, in place of a part of Fe, Ca: 0.0001-0.0015%, Mg: 0.001 to 0.010%, and Rare earth elements: 0.0001 to 0.0100%, Contains one or more selected from the group consisting of Carburized steel parts.

8. A carburized steel part according to any one of claims 5 to 7, The chemical composition of the core portion is, in place of a part of Fe, Te: 0.001 to 0.100%, Bi: 0.001-0.500%, Pb: 0.01-0.09%, Sn: 0.001 to 0.015%, and Sb: 0.001 to 0.006%, Contains one or more selected from the group consisting of Carburized steel parts.

Citation Information

Patent Citations

  • Grain stabilized carburizing steel

    JP1981075551A

  • Steel for carburizing gear

    JP1995126803A

  • Steel for carburizing bearing

    JP1995126804A

  • Steel for carburized gear

    JP1995258793A

  • Steel for gear excellent in resistance to exfoliation, and gear

    JP2010185123A